Mechanical durability and microstructural properties of sustainable high strength mortars ıncorporated basalt fiber and copper slag: Taguchi optimization - Abu Aeshah, Mohammed Naji Ahmed; Kaplan, Gökhan (Elsevier BV, 2022)
This study produced high strength and low CO2 emission mortars using copper slag (CS) as aggregate and Supplementary Cementitious Materials (SCMs). It aims to develop a more environmentally friendly product by using CS both as aggregate and SCMs simultaneously. In addition, it is reinforced with basalt fiber (BF) so that copper waste does not adversely affect its mechanical and durability properties. Taguchi L18 orthogonal test matrix was used in the experimental study. CS was used at 25 and 50% instead of natural aggregate, 7.5%, and 15% instead of cement. BF was added to the mixture in 6 and 12 mm lengths at 1, 2, and 3 ratios. 91-day compressive strengths of the mixtures vary between 41 and 77 MPa. As a result of the optimization, a mixture with a 91-day compressive strength of 81 MPa was obtained. Na2SO4-induced expansions decreased if 15% CS was used instead of cement. Since the water absorption of CS is lower than that of natural aggregate, excessive strength losses after freezing-thawing are prevented. When CS is used as aggregate, drying shrinkage values increase because it reduced the aggregate volume. Air voids smaller than 200 nm were observed in SEM images. It is appropriate to use 7.5% when CS instead of cement and up to 25% when used instead of aggregate. On the other hand, it is appropriate to use up to 2% of BF at a length of 6 mm. Mixtures with a compressive strength of 50 MPa and above can be produced by using CS.